Implementation and validation of an in-house combined fluorescein/media-fill test to qualify radiopharmacy operators - Cyril Fersing; Emmanuel Deshayes; Sarah Langlet; Laurence Calas; Vincent Lisowski; Pierre Olivier Kotzki (SpringerOpen, 2021)
Abstract Background The purpose of this work was to design, validate and implement a media-fill test combined with fluorescein (MFT-F) for the specific qualification and training of radiopharmacy operators, in accordance with United States Pharmacopeia General Chapter 797 and European Good Manufacturing Practices. MFT-F was embedded in the quality management system of our radiopharmacy unit. Its validation involved fluorescein concentration choice, media growth promotion test and evaluation protocol controls (with or without intentional aseptic mistakes). Each operator was evaluated following a three-part evaluation form. Evaluation criteria related to garbing and hygiene, fluorescent contamination and bacteriological contamination (pre- and post-evaluation environment controls and MFT-F samples). Combined MFT-F allowed the assessment of aseptic compounding skills and non-contamination of the working area through a single evaluation. It was also designed to fit the constraints of radiopharmacy common practice related to radiation protection equipment and to the small volumes handled. Results A 0.01% fluorescein concentration was chosen to prepare MFT-F. Addition of fluorescein in the culture medium did not jeopardize its growth properties according to growth promotion test. Eleven operators were evaluated and carried out 3 MFT-F over 3 successive days. Pre- and post-evaluation bacteriological controls of every session showed no CFU of microbiological contaminant above 5. All operators validated the garbing and hygiene evaluation, with an average score of 92.7%. All operators validated the fluorescent contamination evaluation, with an average score of 29.4 out of 30. None of the MFT-F samples showed any visible bacterial growth after incubation. Conclusions Combined MFT-F, as a part of a comprehensive sterile compounding training program, appeared as a convenient and promising tool to increase both the sterile compounding safety and awareness of radioactive contamination in radiopharmacy.